ANALISA KLASIFIKASI LOYALITAS PELANGGAN MENGGUNAKAN ALGORITMA NAÏVE BAYES - Hayuningtyas, Ratih Yulia (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2024)
Customers are one of the important assets in business ventures, every company competes to attract customers by various means of promoting the products they sell. It turns out by focusing on the product it cannot attract customers, therefore the company changed its method become customer-oriented. Looking for information about products in high demand by customers can attract customers to remain loyal to the products sell. To find out whether customers are loyal or not from each visit, you can use a classification algorithm, namely Naïve Bayes. The Naïve Bayes algorithm is one of the best algorithms for classification because it can help find hidden data models during data analysis. In this research, we try to analyze customer data who buy Starbucks to find out which customers are very loyal to buy Strabucks products using the Naive Bayes algorithm. This algorithm groups loyal and non-loyal customer data, then separates it into test data and training data. From this data Testing will be carried out using the Naive Bayes algorithm to determine loyal customers. The results this research have an accuracy value of 87%, a precision value of 90% and a recall of 95%, which means this classification has good performance